2020
DOI: 10.1515/biol-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the heterosis effect on genetic distance, determined using various molecular markers

Abstract: AbstractA number of studies have shown that the greater the genetic diversity of parental lines, the greater the heterosis effect. Genetic or phenotypic variation can be estimated by genotype testing on the basis of the observations obtained through prediction (a priori) or the observations and studies (a posteriori). The first method uses data such as the genealogy of a given subject and the information about its geographical origin. The second method is based on the phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
2
19
0
1
Order By: Relevance
“…Each genotype had a unique banding profile for every AFLP primer combination. These results are in agreement with previous studies on maize using AFLP markers (Oliveira et al, 2004;Legesse et al;2006 Hartings et al;, Neha and Nam, 2016and Tomkowiak, et al, 2020.…”
Section: Aflp Polymorphismsupporting
confidence: 93%
See 2 more Smart Citations
“…Each genotype had a unique banding profile for every AFLP primer combination. These results are in agreement with previous studies on maize using AFLP markers (Oliveira et al, 2004;Legesse et al;2006 Hartings et al;, Neha and Nam, 2016and Tomkowiak, et al, 2020.…”
Section: Aflp Polymorphismsupporting
confidence: 93%
“…From a total of 141 RAPD bands and 276 AFLP peaks, 102 represent 72.3% and 267 represent 96.7% fragments were found to be polymorphic loci, respectively. Also, Tomkowiak, et al (2020) compared the efficiency of AFLP, RAPD markers for determining the relationship among thirteen hybrids and nineteen inbred lines of maize. They obtained 528 AFLP markers and 234 RAPD markers using fifteen primer pairs and forty random oligonucleotide primers, respectively.…”
Section: Genetic Relationships Cluster Analysis Of Rapd Datamentioning
confidence: 99%
See 1 more Smart Citation
“…All organisms are exposed on the influence of different environmental conditions but in the genetic level are the same in all environments. A number of studies have shown that the greater the genetic similarity of parental lines, the smaller the heterosis effect [1]. Genetic or phenotypic similarity can be estimated by genotype testing on the basis of the observations obtained through prediction (a priori) or of the observations and studies (a posteriori).…”
Section: Opinionmentioning
confidence: 99%
“…Four continents including America, Europe, Australia and Asia are important for food cultivation as oil and meal while non-food uses are as biofuel or lubricants. It stands second world crop after soybean (Jan et al 2017, Tomkowiak et al 2020. The close relationship between six particularly important species (Brassica carinata, B. juncea, B. oleracea, B. napus, B. nigra and B. rapa) was described by the triangle of U theory (UN 1935).…”
Section: Introductionmentioning
confidence: 99%